PARTICULARITIES OF TREATMENT OF ASSOCIATED TRAUMA OF MID-FACE AND DEFORMITIES - Skikevych, M.G.; Voloshyna, L.I. (World of Medicine and Biology, 2013)
Due to the topographicanatomicalclinical manifesta-tions,mid-face injuriesare extremely diverseand complex. The prognosis for the general state of body might be severe. The main task for the diagnostics and treatment planning of the injuredis to obtainan accurate idea about changes in bone and soft-tissue structures of the face. Life-saving measure sare of vital importance as well as detection and prediction of the effects of various injuries.There might be cases of delayed visits to doctor which lead to complications. Efficient planning of complex treatment and creation of individual mechanisms/system sare crucial for the proper diagnostics and successful treatment. Stereolithography method significantly enhances modern osteoplastic surgery and facilitate introduction of new types of implants.
Keywords: trauma of the mid-face; statistics; comprehensive examination; surgical treatment; deformity; complications